Pengaruh Kesadaran Lingkungan, Ekolabel, dan Green Price Terhadap Keputusan Pembelian Ecofrenbag - Baharmi, Hasibah; Purwanto, Edy (Journal MISSY (Management and Business Strategy), 2024)
In today's age of globalization, global warming has a health impact, where global warming is triggered by human immorality that doesn't care about the environment. By using eco-friendly products, we can minimize the amount of garbage accumulated by turning it into compost. The objective of this study is to study the influence of environmental awareness, eco-label, dang green price on the decision to buy Ecofrenbag. The sampling techniques used were purposive samplings and using the roscoe formula to determine the number of populations, in this study obtained 100 respondents. The results of this study show that environmental awareness and green prices have a significant influence on purchasing decisions, while eco-labels have no significant impact on purchase decisions. The known R Square value is 0.624, which means that environmental awareness, eco-label, and green price influence purchasing decisions by 62.4%, and the remaining 37.6% is influenced by other variables not studied in this study.